Efektifitas Pembelajaran Ditinjau Dari Pelaksanaan Supervisi - Fitriadi Lubis (Ta'dib, 2016)
The purpose of this research is to examine the relationship between teachers’ perception about supervision and teaching effectiveness. The data was obtained from 40 teachers. The instrument used in this research was questionnaire. The data was analyzed by using SPSS proram. The result of this study shown that the correlation between teachers’ perception about supervision and teaching effectiveness was 0.43. the contribution of teachers’ perception variable was 0.18% to teaching effectiveness variable.